226 Comorbidity in systemic lupus erythematosus. (April 2019) - Egeli, Bugra; Soykut, Asli Ece; Ugurlu, Serdal
Abstract : Background: In Systemic Lupus Erythematosus (SLE), cardiovascular mortality is important. In our previous study, we observed atherosclerotic plaque formation in carotid and/or femoral artery in SLE patients. 1 The aim of this study was to assess the comorbidity of the patients diagnosed with SLE over 10 years. Methods: The sample group is a subset of 2009 study. In 2009, the patients who already had myocardial infarction or cancer diagnosis were excluded. The patients were interviewed with polar questions of whether they were diagnosed with acute myocardial infarction (AMI), cerebrovascular events, cancer, diabetes, and hypertension. Results: We studied 65 patients (56F, 9 M; mean age: 53±8.76) with SLE diagnosis. In 2009, out of 94 SLE patients we included in the study, 2 (2.13%) of the patients were diagnosed with diabetes, and 33 (35.11%) with hypertension. However, in 2018, out of the 65 patients we reached, 8 (12.31%) with diabetes, and 37 (56.92%) with hypertension. The increase in diabetes and hypertension was found significant. (p=0.009 and 0.006) The table 1 shows the percentages of newly occurred cancer, angina pectoris, and AMI/Stroke events. Conclusions: In 10 year follow-up, the significant increase in hypertension and diabetes can show us a sign of atherosclerotic plaque formation. However, the increased hypertension and diabetes ratio can still be due to increased age. Funding Source(s): None Reference: Ugurlu S, Seyahi E, Cetinkaya F, Ozbakir F, Balci H, Ozdogan H. Intima-media thickening in patients with familial Mediterranean fever. Rheumatology (Oxford) . 2009 August;48(8):911–5.